CARDIOPULMONARY TEST PARAMETERS USEFUL FOR ADDRESSING PATIENTS WITH PECTUS EXCAVATUM TO PROMOTION OF PHYSICAL ACTIVITY. (June 2022) - Pellegrino, Alessio; Casatori, Lorenzo; Messineo, Antonio; Ghionzoli, Marco; Facchini, Flavio; Modesti, Alessandra; Modesti, Pietro Amedeo
Abstract : Objective: Exercise training increases muscle VO2 by increasing O2 transport and O2 uptake positively affecting cardiac output. In subjects with pectus excavatum cardiac output increase during exercise might be limited by the conformation of the chest. In this condition, the psychological impact of the deformity can further reduce the propensity to physical activity, leading to a sedentary lifestyle. Surgery is the preferred choice in severe cases. However, many patients with milder deformities can benefit from exercise-based treatment. The choice of the therapeutic strategy is fundamental, but the functional parameters on which to base this choice are not yet well defined. Therefore, we investigated the relationships between habitual physical activity and functional physiological parameters obtained from the cardiopulmonary exercise test (exercise performance and stroke volume at peak exercise) in pectus excavatum. Design and method: A cohort of adolescents (15 with pectus excavatum and 15 age- and sex-matched healthy controls) underwent Cardiopulmonary Exercise Test to estimate exercise performance (VO2 max) and stroke volume at peak exercise (VO2/HR, O2 pulse). Habitual weekly physical activity, estimated with International Physical Activity Questionnaire – Short Form (IPAQ-SF), was expressed as METs h-1·week-1. Determinants of exercise performance and stroke volume at peak exercise were investigated in the whole group with multivariable linear regression analysis adjusted for sex, body mass index, forced expiratory volume in the first second, and presence of pectus excavatum. Results: When compared to healthy controls, subjects with pectus excavatum had lower VO2 max (37.2 ± 6.6 vs 45.4 ± 6.4 mL·kg-1·min-1, p < 0.05), and O2 pulse (12.1 ± 2.4 vs 16.2 ± 3.6 mL·min-1·bpm-1, p < 0.05). Importantly, physical activity level was a predictor of VO2 max (B = 0.085; 95% Cl 0.010 to 0.160) while it did not affect O2 pulse (B = 0.035; 95% Cl -0.004 to 0.074). Conclusions: Training programs should be encouraged to increase cardiopulmonary performance in subjects with pectus excavatum. A marked reduction in O2 pulse at peak exercise might be considered as a criteria to address a subject towards surgery.